Sedekah Wajibah dalam Zakat Hewan Ternak: Sebuah Tinjauan Hadits tentang Zakat - Ahmad Alamuddin Yasin (Mutawasith: Jurnal Hukum Islam, 2022)
This paper aims to examine more deeply the meaning of the Hadith context of the obligation of zakat in the form of a letter written by Abu Bakr R.A on the orders of the Prophet. The research method used by the author is to use qualitative research methods. Meanwhile, when viewed from the research sources, this research can be categorized as library research. The results of this study indicate that the purpose of zakat which is to be herded as described by Wahbah Zuhaili is to be fat, reproduce quickly and in large numbers. Meanwhile, this does not apply in Indonesia because the conditions in Indonesia now and at the time of the Prophet are very different. Shepherd or not, livestock in Indonesia must be issued zakat.